“... And even in heaven, sir...”The tondero: towards an understanding of the duality of gender - Yep Lenginnam, Virginia Beatriz (2018)
In Piura the tondero is the traditional dance and the banda the most representative instrumental ensemble. This article presents an analysis of this genre in its two variants: the tondero de los criollos, sung and accompanied by guitars and cajón, and the tondero de banda, played by the banda de músicos according to the principles established by the estilo de banda. I will begin by explaining the stylistic aspects of each group to outline a definition of the genre that considers its duality. Then I will analyze the main characteristics of each variant to enter into a musical analysis that compare the coincidences and differences of both variants. I finish with a final reflection.